연구자들은 K-댄스를 어떻게 바라보는가: 학술연구 텍스트 분석을 활용하여 - 김동근(Dong-geun Kim); 김정환(Junghwan Kim); 최홍규(Hong-Gyu Choi) (디지털콘텐츠학회논문지, 2024)
본 연구는 K-댄스 연구 동향을 종합적으로 파악하기 위해 KCI 등재지 및 KCI 등재후보지에 수록된 82건의 K-댄스 관련 학술논문의 초록을 분석하였다. K-댄스와 관련한 연구 동향을 파악하고, K-댄스 관련 키워드들이 학술연구의 맥락 속에서 어떠한 관계를 갖는지 살펴보기 위해 단어빈도분석, TF-IDF분석, 동시 출현 빈도 분석, LDA토픽모델링을 활용하였다. 분석 결과, K-댄스 학술연구는 K-팝의 흥행과 함께 연구 수가 증가하는 경향을 보였다. 주요 연구 분야는 무용, 문화산업, 체육 분야 등이었다. ‘무용’, ‘교육’, ‘스트릿댄스’가 다빈도 키워드로 도출되었으며, 동시 출현 빈도 분석을 통해 다양한 분야에서 K-댄스에 관한 논의가 진행되고 있음을 확인하였다. 또한, LDA토픽모델링 결과 ‘스트릿댄스의 발전’, ‘디지털 콘텐츠로서의 댄스’, ‘창작물로서의 댄스’ 등으로 주제가 구분되었다. 연구 결과, K-댄스가 학술적, 교육적, 그리고 문화적 가치를 지닌 중요한 연구 분야로 자리 잡고 있다는 점을 확인하였다. 반면에 K-댄스 분야에 종사하는 댄서, 안무가의 권리와 안무 저작권에 관한 연구는 상대적으로 부족함을 확인하였다. This study analyzed the abstracts of 82 academic papers related to K-dance included in KCI-registered journals and KCI-registered candidates to comprehensively understand the trends in K-dance research. Word frequency analysis, TF-IDF analysis, co-occurrence frequency analysis, and LDA topic modeling were used to identify research trends related to K-dance and examine the relationships between keywords related to K-dance in the context of academic research. The data revealed that the number of academic studies on K-dance increased along with the popularity of K-pop. The primary research fields were dance, cultural industries, and sports. “Dance,” “education,” and “street dance” emerged as prevalent keywords, and the co-occurrence frequency analysis confirmed that discussions on K-dance are active in various fields. Additionally, the results of LDA topic modeling were divided into topics such as “development of street dance,” “dance as digital content,” and “dance as a creative work.” The study’s findings confirmed that K-dance constitutes a significant area of study with academic, educational, and cultural values. Conversely, the study revealed a relative lack of research on the rights of dancers and choreographers working in the K-dance field and on choreography copyrights. KCI Citation Count: 0